1989
DOI: 10.1021/ja00186a058
|View full text |Cite
|
Sign up to set email alerts
|

Spiropentane as a tensile spring

Abstract: Health for financial support (GM 30757) and . K. O'Brien thanks the Graduate Alumni of Case Western Reserve University for the award of a Graduate Fellowship (August 1987-May 1988. Supplementary Material Available: Structural report for compound 6 giving methods for data collection, data reduction, structure solution and refinement, tables of crystal data, intensity measurements, structure solution and refinement, positional and thermal parameters, general temperature factor expressions, bond distances, bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
4

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 0 publications
1
35
0
4
Order By: Relevance
“…Seine Abmessungen wurden in der Gasphase über Elektronenbeugung (ED), [80] an mindestens zwei flüssigkristallinen Phasen (LC) über NMR-Spektroskopie [80][81][82][83] und über Tieftemperatur-Einkristall-Rçntgenbeugung [84] (Fp. Seine Abmessungen wurden in der Gasphase über Elektronenbeugung (ED), [80] an mindestens zwei flüssigkristallinen Phasen (LC) über NMR-Spektroskopie [80][81][82][83] und über Tieftemperatur-Einkristall-Rçntgenbeugung [84] (Fp.…”
Section: Koordination Von Zwei Tertiären Phosphanen An Einem Kohlenstunclassified
See 1 more Smart Citation
“…Seine Abmessungen wurden in der Gasphase über Elektronenbeugung (ED), [80] an mindestens zwei flüssigkristallinen Phasen (LC) über NMR-Spektroskopie [80][81][82][83] und über Tieftemperatur-Einkristall-Rçntgenbeugung [84] (Fp. Seine Abmessungen wurden in der Gasphase über Elektronenbeugung (ED), [80] an mindestens zwei flüssigkristallinen Phasen (LC) über NMR-Spektroskopie [80][81][82][83] und über Tieftemperatur-Einkristall-Rçntgenbeugung [84] (Fp.…”
Section: Koordination Von Zwei Tertiären Phosphanen An Einem Kohlenstunclassified
“…[84] Der Einfluss von Substituenten auf die relative Länge der vicinalen und distalen C-C-Bindungen kann hin-gegen beträchtlich sein, und diese Effekte kçnnen in quantenchemischen Rechnungen erfasst werden. Kristallpackungseffekte führen kaum zu Verzerrungen; deshalb wurde das Molekül auch als "dehnbare Feder" bezeichnet.…”
Section: Koordination Von Zwei Tertiären Phosphanen An Einem Kohlenstunclassified
“…42 The experimental molecular geometry of spiropentane has been well established by electron diffraction in the gaseous state, 43,44 by NMR in the nematic phase 45,46 and also by x-ray analysis of unsubstituted spiropentane 47 and derivatives 48 in the crystalline state. HF, MP2 and DFT-B3LYP calculations of molecular geometry, isotropic magnetic shieldings (chemical shifts) and vibrational frequencies were recently performed by Dodziuk et al 49 In addition, the gas-phase protonation of spiropentane to yield C 5 H 9 C ions has been investigated by -radiolysis and FT-ICR techniques combined with ab initio calculations, 50 and also spiropentane radical cation was isolated and investigated in a CCl 3 F matrix at 4 K. 51 Going back to Table 1, spiropentane possesses the highest molecular symmetry D 2d and the largest deviation of the inter-ring bond angle at the spiro carbon (ca 137°) from the tetrahedral geometry in the series 1-7.…”
Section: Spiro[22]pentane (1)mentioning
confidence: 99%
“…Ł level in comparison with those calculated at the HF, MP2 and B3LYP levels by Dodziuk et al 49 and determined experimentally by x-ray, 47 electron diffraction 43 and NMR in the nematic phase 45 are compiled in Table 2. Very good agreement of the present results with the x-ray experimental geometry was found, in line with the reported MP2 and B3LYP data.…”
Section: Spiro[22]pentane: Benchmark Calculationsmentioning
confidence: 99%
“…3 The I3C NMR spectrum showed that it has C2 symmetry2 and indicated the bridgehead hydrogens to be trans.…”
mentioning
confidence: 99%